Mucins and associated glycan signatures in colon adenoma–carcinoma sequence: Prospective pathological implication(s) for early diagnosis of colon cancer. Issue 2 (1st May 2016) - Krishn, Shiv Ram; Kaur, Sukhwinder; Smith, Lynette M.; Johansson, Sonny L.; Jain, Maneesh; Patel, Asish; Gautam, Shailendra K.; Hollingsworth, Michael A.; Mandel, Ulla; Clausen, Henrik; Lo, Wing-Cheong; Fan, Wai-Tong Louis; et al.
Highlights: Comprehensive study of mucins and associated glycans during colon carcinogenesis. Significant alteration of mucins MUC4, MUC17, MUC2, MUC5AC and glycans Tn/STn-MUC1. MUC2/MUC5AC/MUC17 panel discriminates adenoma/adenocarcinoma from benign polyps. Abstract: Development of biomarkers that detect early stage resectable premalignant lesions of colon can provide critical aid in the prevention of colorectal cancer. Recent lines of evidence suggest the utility of mucin expression to predict malignant transformation of colon pre-neoplastic lesions. In this study, we investigated the combined expression of multiple mucins and mucin-associated glycans during the adenoma–carcinoma sequence of colon cancer progression. Further, we evaluated their applicability as markers for differentiating adenomas/adenocarcinomas from hyperplastic polyps. Immunohistochemical analyses performed on colon disease tissue microarrays revealed downregulation of MUC2 and MUC4 expression (p < 0.0001) while MUC1 and MUC5AC expressions were upregulated (p = 0.01) during adenoma–adenocarcinoma progression. Expression of MUC17 was downregulated in inflamed tissues compared to normal tissues, but its increased expression differentiated adenomas (p = 0.0028) and adenocarcinomas (p = 0.025) from inflammation. Glycan epitope-Tn/STn on MUC1 showed higher expression in hyperplastic polyps (p = 0.023), adenomas (p = 0.042) and adenocarcinomas (p = 0.0096) compared to normal tissues. Multivariate regression analyses indicated that a combination of MUC2, MUC5AC, and MUC17 could effectively discriminate adenoma–adenocarcinoma from hyperplastic polyps. Altogether, a combined analysis of altered mucins and mucin-associated glycans is a useful approach to distinguish premalignant/malignant lesions of colon from benign polyps.